ENGLISH READING COMPETENCE THROUGH SCIENTIFIC APPROACH IN THE 2013 ENGLISH CURRICULUM IMPLEMENTATION - Puput Gunadi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
The objective of this research is to identify whether: (1) Video Voice Command (VVC) multimedia can improve students’ reading competence; and (2) to describe the class situation when the interactive multimedia is used in the teaching and learning process of reading competence in the class. The research was conducted in SMA N 1 Purwareja Klampok, Banjarnegara regency. The subjectwas the first grade students of language program consisted of 37 students in the second semester of 2014/ 2015 academic year. This classroom action research was conducted with two cycles whicheach cycle had three meetings. The procedures of the research consisted of planning, acting, observing, and reflecting. The result of the research shows that (1) Video Voice Command (VVC) multimedia could enhance students’ reading competence in term of raising students’ achievement in the case of finding out (a) explicit information, (b) reference of pronouns, (c) communicative purposeof the author, (d) words’ meaning, (e) main idea in the paragraph, and (f) implicit information in the text; and (2) the interactive multimedia could enhance class situation, in term of (a) the students’ attention that make them concentrate on the lesson, (b) their participation and interaction when having and responding teacher’s questions, (c) the motivation to join the teaching and learning process in the class.